The Use of Oral Means in the Novel “Qoraquyun” (Texas Journal of Multidisciplinary Studies, 2022)
The novel "Qoraquyun" includes rich lexical groups according to lexical features. The vocabulary of the novel consists mainly of widely used words, archaic words. In the novel, words specific to the literary style are also used. Scientific speech, which is available in other speech styles, has almost no tools specific to formal speech. However, oral means of speech can be found in many of the pages of the novel. The lexical reliance mainly on widely used words and means of oral discourse leads to the conclusion that the novel aims to express ideas in a form that is linguistically simple, close to the vernacular.